Dampak Tari Budaya Gayo Tari Saman dalam Tradisi Islam di Desa Titi Pasir Kecamatan Semadam Kabupaten Aceh Tenggara - Husaini, Alpahmi; Kamaluddin, Kamaluddin; Fitriani, Fitriani (YASIN, 2023)
This research examines the cultural impact of the Gayo saman dance on the Islamic tradition in Titi Village. This type of research is field research (research in the field) which is a research carried out by collecting data by research at locations where there are symptoms that will be examined to find facts found in society. The results of this study are that the Saman Gayo dance choreography is not an ordinary dance work, but Saman is a dance that contains basic Islamic concepts symbolized through rhythm, movement, poetry, floor patterns, clothing, stages of performance, purpose of offerings. From the choreography produced, it can be seen that the Saman Dance is a symbol of the Gayo tribe in carrying out Islamic law in their daily lives, so that the Saman Dance is synonymous with Islam and in accordance with the customary system in Acehnese society, namely "adat with syaraad, syaraq with Kitabullah". This statement becomes clear by looking at the performance of the Saman dance itself, which was originally an activity of the Gayo people in taking advantage of the time between their breaks by playing a game which was later called pok ane. This game later became a medium for spreading the teachings of Islam, especially in the Gayo Lues highlands. The lyrics mean advice, religious advice, rules that guide life, and so on. This dance is a symbol of brotherhood, education, religion, courtesy, heroism, cohesiveness, and togetherness. Through the Saman dance, the community is taught to behave according to politeness in Islam which is also in accordance with the customs that apply to the Gayo tribe.